2004
DOI: 10.1016/j.anbehav.2003.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Grooming as a reward? Social function of grooming between females in cooperatively breeding marmosets

Abstract: Classical models of grooming predict that subordinate primates will direct grooming towards dominants to receive coalitionary support from them. In contrast, recent reviews suggest that grooming asymmetries can change with social system and ecological conditions and should reflect asymmetries in services provided by different members of the dyad. We studied grooming patterns between females in six wild groups of common marmosets, Callithrix jacchus, to investigate the relation between social structure and groo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 42 publications
8
80
2
3
Order By: Relevance
“…We found that allogrooming reciprocity within the dominant pair was significantly higher than that observed between breeding males and subordinate females, and between dominant and subordinate females. Also, males were the main groomers in all three groups, as recorded for six groups (group Q in a different period, and five other groups) in the same field area [Lazaro-Perea et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…We found that allogrooming reciprocity within the dominant pair was significantly higher than that observed between breeding males and subordinate females, and between dominant and subordinate females. Also, males were the main groomers in all three groups, as recorded for six groups (group Q in a different period, and five other groups) in the same field area [Lazaro-Perea et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…In a field study Lazaro-Perea et al (2004) reported that common marmosets groom down the hierarchy with breeding adults grooming helpers significantly more than the reverse. Since grooming behavior releases betaendorphins (Keverne et al, 1989) and oxytocin (Carter, 1998), both of which provide reinforcing effects, high levels of grooming of helpers by breeding adults can be seen as providing direct physiological reinforcement to helpers.…”
Section: Social Mechanisms Maintaining Helpersmentioning
confidence: 99%
“…5 breeders may specifically use grooming as incentive for helpers to stay in the group [32][33][34].…”
Section: Accepted Manuscriptmentioning
confidence: 99%